Epitaxial Crystallization Behaviors of Various Metals on a Graphene Surface. Issue 14 (4th May 2016) - Kim, Dae Woo; Kim, Seon Joon; Choi, Hyung Ouk; Jung, Hee‐Tae
Abstract : Epitaxial crystallization of metals is demonstrated on graphene. Face‐centered cubic metals like Ni, Au, Cu, and Pt display a preferred orientation along the [111] direction, whereas Fe, with a body‐centered cubic structure, displays a preferred orientation along the [100] direction. Epitaxially crystallized metal film on the three dimensional supports is achieved through a simple coating of the support with graphene.